Synthesis and Evolution of Zirconium Carbide via Sol–Gel Route: Features of Nanoparticle Oxide–Carbon Reactions. Issue 4 (19th March 2013) - Ang, Caen; Williams, Tim; Seeber, Aaron; Wang, Huanting; Cheng, Yi‐Bing; Fahrenholtz, W.
<x xml:space="preserve">Abstract</x> A sol–gel route was used to synthesize nanocrystalline zirconium carbide (ZrC). The starting materials were zirconium propoxide, with carbon introduced by furfuryl alcohol (FA). A block copolymer surfactant was used to homogenize the oxide and carbon components. ZrC was produced at a low temperature of 1250°C and complete conversion achieved at 1450°C. The powder was nanocrystalline size less than 100 nm. Phase changes were studied using X‐ray diffraction and Raman spectroscopy. Rietveld analysis followed the changes in crystallite size and lattice parameters of the phases during carbothermal reduction. Morphology changes were observed using nitrogen gas sorption. High‐resolution TEM and EDS were used to image the carbide lattice, surface oxides, and graphene‐like carbons. The results indicate that nanoparticle carbothermal synthesis involves agglomeration and necking as the most viable mode of mass transport to complete the carbothermal reduction.